Characterization and ecological leaching to recover precious metals in amalgamation tailings – Puno - Ortiz Barreto, Jorge Alberto (2023)
The gold-silver artisanal operations carried out throughout the Peruvian territory are characterized by having low recoveries of precious metals, being carried out in poor working conditions and generating negative consequences in the ecosystem, which was the basis of the approach to our problem. For this, a representative sample of a batch of amalgamation tailings in the department of Puno was investigated with a tested head of 19.58 gr/TM of Au, 159.67 gr/TM of Ag and 10.53 ppm of Hg. The optical microscopy report indicated the presence of gold, pyrite, magnetite, hematite, Ilmenite, rutile and gangue. With the results of the mineralogical characterization, leaching tests were carried out with ecological reagents for a sample with a regrind granulometry of 87 microns, such as: Sandioss, which reached a recovery of 99.25% Au and 93.14% Ag, with a consumption of 22.56 kg/TM for a period of 24 hours. Under the same operating conditions, the Jinchan reagent was evaluated, achieving a recovery of 96.31% Au and 91.18% Ag, with a consumption of 18.57 kg/TM. The conventional cyanide leaching process achieved a recovery of 97.76% Au and 92.96% Ag, for a consumption of 17.83 Kg/TM.